Analisis Pola Konsumsi Daging Sapi Pada Masyarakat Pesisir di Kabupaten Tanjung Jabung Timur - F, Firmansyah; Farhan, Muhammad (Fakultas Peternakan Universitas Jambi, 2014)
Â The meat consumption pattern of costal community in the regency of Esat Tanjung Jabung was chicken, beef, fish, anchovy, wet shrimpÂ ,, freshwater fish and salted fish. The beef consumption was around 8.03 g percapita perday. Family habit in consuming beef, family taste in consuming beef, the family in-come percapita and the meat availaibity simultaniously affects on meat consumption in this area. However in partial family income is the only factor affecting the meat consumption on costal community in the regency od East Tanjung Jabung.